The Effect of Sociodemographic and Unhealthy Behaviour Factors on the Pharmaceutical Expenditure Share by Households in Malaysia - Ang, Wei Chern (2022)
The third United Nations Sustainable Development Goal (SDG) seeks to improve universal access to medicines. In Malaysia, out-of-pocket expenditure is the highest for private total health expenditure, which includes pharmaceutical products. However, it is unknown how likely and profound the monthly spending is, relative to household income. The objectives of this study are to investigate the sociodemographic and unhealthy behaviour factors associated with pharmaceutical expenditure share (PES) among households in Malaysia generally, among different income groups and different regions by Gross Domestic Product (GDP) per capita. This study used Household Expenditure Survey 2014 microdata analysed mainly by two-part models (probit and ordinary-least square regressions). All households (n=14,838) had a PES of 0.94%, or a mean expenditure of RM 31.53. 43.8% of households purchased pharmaceuticals with a PES of 2.15% or a mean expenditure of RM 71.95. Bivariate analysis shows that age, ethnicity, education and employment status of household heads, residing strata, household income and regions by GDP per capita were significantly associated with PES. Unemployed, female (middle-income states), single household heads (M40 and T20 households) and having a large household increased the likelihood of pharmaceuticals consumption. Increasing age, female (high-income states), increasing education of household heads, and decreasing household income increased PES. Non- Bumiputera households and consuming sugary products increased both the likelihood and allocation on pharmaceuticals. Similarly, those residing in middle-income states were more likely to spend, and spent more of their income than households in lowincome states. In contrast, urban households were less likely to spend, but spend more. More public health clinics in urban areas and townships with many retirees in middleincome states while intensifying the existing ‘Know your medicine’ campaign to large families are among the recommendations suggested from this study.